Nuevos modos de escritura digital en estudiantes de bachillerato del colegio Carmen Mora de Encalada de la ciudad de Pasaje - Correa Chuchuca, Jessica Yamileth; Figueroa Parra, Jessica Mishell (Machala, 2023)
The use of new technologies and communication is changing every time, especially in the use of the Internet, which has become a daily tool for people in the world in general, because it facilitates communication and exchange of information quickly and easily. Nowadays, the new ways of writing in students has become a real problem in the classroom, the main purpose of this project is to reflect on the proposed topic and to know the new forms of digital writing in high school students of the Carmen Mora de Encalada School in the city of Pasaje. Through that to know their faults in misspelled words and to avoid that they do not continue using bad spelling in the writing requested by the teacher. This research is reliable, responsible and truthful, based on a field work taking as a reference the actors themselves as a fundamental piece of the high school students of the City of Pasaje. By means of that to know their faults in misspelled words and to avoid that they do not continue to use the bad spelling in the writings that the teacher requests. This research is reliable, responsible and truthful, based on a field work taking as reference the actors themselves as a fundamental piece to the high school students of the City of Pasaje. It is possible to identify how the factors influence adolescents who have created the new modes of digital writing when sending a message, writing a comment or posting a photo either by Whatsapp, Facebook, TikTok and Instagram. We took into consideration a qualitative and quantitative methodology in which we used instruments for collecting information through surveys and interviews with teenagers and professionals, which allow us to identify the new words used by students that will help us in the field of research
El uso de las nuevas tecnologías y comunicación cada vez va cambiando, sobre todo en la utilización del internet que se ha convertido en un instrumento cotidiano de las personas del mundo en general, debido a que facilita comunicarse e intercambiar información de manera rápida y sencilla. Ahora en la actualidad los nuevos modos de escritura en los estudiantes, se ha convertido en un verdadero problema dentro de las aulas de clases, el propósito fundamental de este proyecto tiene como finalidad buscar reflexionar sobre el tema propuesto y conocer las nuevas formas de escritura digital en estudiantes de bachillerato del Colegio Carmen Mora de Encalada de la Ciudad de Pasaje. Mediante eso saber sus falencias en palabras mal escritas y evitar que no sigan usando la mala ortografía en las redacciones que solicita el docente. Esta investigación es confiable, responsable y veraz, basada en un trabajo de campo tomando como referencia a los propios actores como pieza fundamental a los estudiantes de bachillerato de la Ciudad de Pasaje. Se puede identificar como los factores influyen en adolescentes que han creado los nuevos modos de escritura digital al momento de enviar una mensaje, escribir un comentario o publicar una foto ya sea por Whatsapp, Facebook, TikTok e Instagram. Se tomó en consideración una metodología de carácter cualitativa y cuantitativa en la que se utilizó instrumentos de recolección de la información mediante las encuestas y entrevista a los adolescentes y profesionales, las cuales nos permiten identificar las nuevas palabras que usan los estudiantes eso nos ayudará en la investigación de campo.
Keywords: NUEVAS FORMAS DE ESCRITURA DIGITAL; NARRATIVAS DIGITALES; COMUNICACION DIGITAL; REDES SOCIALES; INTENCIONALIDAD COMUNICATIVA